2016
DOI: 10.1186/s12879-016-1630-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility and genomic variations in Staphylococcus aureus associated with Skin and Soft Tissue Infection (SSTI) disease groups

Abstract: BackgroundStaphylococcus aureus is associated with human skin and soft tissue infections (SSTIs); however, the involvement of virulence factors in different clinical presentations is unclear.MethodsWe analyzed methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA) strains from Taiwan to determine correlations among the clinical characteristics of SSTIs, antimicrobial susceptibility and virulence factors of S. aureus with specific genetic backgrounds.ResultsWe identified 177 MRSA isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
3
12
0
5
Order By: Relevance
“…This pathogen is the etiological agent of several different systemic infections, affecting skin and soft tissue, as well as musculoskeletal and circulatory systems (Lowy, 1998; Changchien et al, 2016). It was reported that S. aureus can survive in human monocyte-derived macrophages (Kubica et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This pathogen is the etiological agent of several different systemic infections, affecting skin and soft tissue, as well as musculoskeletal and circulatory systems (Lowy, 1998; Changchien et al, 2016). It was reported that S. aureus can survive in human monocyte-derived macrophages (Kubica et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is a leading cause for wide range of mild skin infection to endocarditis or necrotizing pneumonia in the hospital and communities [1]. Methicillin, the first synthetic penicillin was used in 1961 for the treatment of S. aureus infections and methicillin resistant strains appeared from hospitals in this year.…”
Section: Introductionmentioning
confidence: 99%
“…Hastane kökenli MRSA enfeksiyonlarının aksine toplum kökenli MRSA suşlarında en önemli virulans faktörü Penton Valentine Lökosidin (PVL) sentezi kabul edilmektedir (6)(7)(8)(9) . PVL pozitif suşların doku nekrozu ve abse formasyonu ile ilişkili olduğu göz-lenmiştir (7) .…”
Section: Discussionunclassified
“…Elbette ki, trimetoprim sulfametaksazol, klindamisin ve uzun etkili tetrasiklinler kullanımı devam eden ancak yapılan çalışmalar ile tedavi başarısı tam olarak kanıtlanamamış antibiyotikler de tedavide yerini korumaktadır (1) . Klindamisin, HK-MRSA suşlarında yüksek direnç nedeniyle tercih edilmemektedir, ancak yapılan bazı çalışmalar TK-MRSA absesi olan çocuklarda etkili olduğu gös-terilmiştir (9,(14)(15)(16) . Hastamızda öncelikle ampisilin sülbaktam-klindamisin antibiyoterapileri uygulanmış olup, kültür sonucunda direnç görülmesi üzerine duyarlı olduğu teikoplanin tedavisine geçilmiştir.…”
Section: S Baysal Ve Ark Toplum Kökenli Metisilin Dirençli Staphylunclassified